Spatial Analysis of Competency Approach as an Entrepreneurial Distinctiveness: A Focus on Micro and Small Enterprises - Francis Jr. M. Tabor; Xavier Lawrence D. Mendoza; Jerico B. Tadeo (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2023)
Micro and Small enterprises provide an essential role in the Philippine economy by creating more job opportunities that help reduce the country's poverty rate. However, with numerous competitors, MSEs with entrepreneurial distinctiveness only tend to continue their business operations. Thus, this study aimed to assess and understand the entrepreneurial competencies and distinctiveness of DTI-registered MSEs in selected areas in Cavite. This study utilized a descriptive correlation research design. A stratified sampling technique was employed to determine the specific quality of the participants. This study used 385 DTI-registered MSEs as respondents in selected Cavite areas. The study's findings stated that MSEs have enough entrepreneurial competence for the sustainability and continuity of their business operation. This study concluded that MSEs have more significant differences regarding the opportunity, organizing, relationship, and commitment than strategic and conceptual competency between the business profile. Thus, the researchers recommend that MSEs further develop the six dimensions of entrepreneurial competency mentioned in this study by attending training programs and seminars regarding the proper utilization and execution of entrepreneurial competencies that may increase business performance and growth. Moreover, local government agencies responsible for policy-making and related agencies conducting seminars and training programs consider proposing assistance to MSEs related to awareness and understanding of different dimensions of entrepreneurial competencies and proper utilization and generation of competitive advantage recognition of a business owner. Keywords: competency approach, entrepreneurial competency, entrepreneurial distinctiveness, micro and small enterprises (MSEs)